Effect Of Garlic Extract (Allium sativum) Histopathology Description Of The Breast In Female White Rats Sprague-Dawley Strain Induced 7,12 Dimetilbenz(a)antrasen (DMBA) - Dewanti, Intan Putri; Damanik, Efrisca M. Br.; Amat, Anita Lidesna Shinta (Universitas Nusa Cendana, 2023)
Background: Cancer is one of leading cause of death number 2 in the world,or one of the six deaths in the 2018. The incidance of breast cancer as much as 11,6% and the number of death are 6,6% in 2018. Medical plant be expacted has potential as an anticancer with minimal side effects when used at the correct dosage, timing and when used it properly. Objectives: To determine the effect of garlic extract on the histopathological picture of female Sprague-Dawley rats induced DMBA. Methodology: This study used an experimental method with a post test only control group design approach using 6 treatment groups. The number of samples was 30 rats with each group containing 5 rats. All data were analyzed using the Shapiro- Wilk normality test followed by the Kruskal Wallis non-parametric test. Results: The results showed that there was no effect on the administration of garlic extract on the histopathological picture of female Sprague-Dawley rats induced DMBA. Group 1 there was no change in the ductal epithel. Group 2 there were changes in the ductal epithelium to hyperplasia with atypia. Group 3, group 4, group 5, group 6 there were changes in the epithelial ducts up to severe hyperplasia. The results of the Kruskall-Wallis statistical test showed that there were no significant differences between groups (p> 0.05). The results of the Mann-Whitney post hoc test in groups 1 and 2 showed a significant difference (p <0.05). Conclusion: DMBA induced can cause changes in the histopathological picture of female Sprague-Dawley rats breast. There was no effect of garlic extract on the histopathological picture of the female Sprague-Dawley rats breasts induced by DMBA.